Gene‐based polymorphisms reveal limited genomic divergence in a species with a heritable life‐history dimorphism. Issue 4 (July 2015) - Zakas, Christina; Rockman, Matthew V.
SUMMARY Understanding the genetic basis of life‐history traits is a long‐standing goal of evolutionary biology. Many closely related species have contrasting life‐history strategies, suggesting that the switches in early development that lead to divergent life‐histories evolve quickly and frequently. Life‐history changes that originate in early development have profound downstream effects on a species' morphology, ecology, genetic diversity, and even speciation rate. How do such transitions in development mode occur, and what is the underlying genetic architecture? To begin to address these questions, we investigated genetic variation in an emerging model in developmental evolution, the polychaete Streblospio benedicti, which has two contrasting and highly heritable offspring types. We compare transcript‐based SNP genotypes of individuals of the two development modes to determine the extent of genomic differentiation between them. We find that there is extensive allele sharing across the two types, and minimal fixed differences. We use the site frequency spectrum to fit demographic models to our data and determine that there is recent gene flow between developmental morphs. Our data suggest that the evolution of a genetic developmental dimorphism is not associated with longstanding genetic isolation or genomically extensive divergence. Rather, differences at developmentally important loci, or modest allele‐frequency differences at many loci, may be responsible for the drastic life‐history differences.